COVID-19 AND KIDNEY DAMAGE - Azizova Shoira Kayumovna; Haydarov Sanjar Nizomitdinovich (Galaxy International Interdisciplinary Research Journal, 2022)
The review provides data on the frequency and causes of the onset and development of acute kidney injury (AKI) in COVID -19. A review of the available scientific information regarding the occurrence and / or progression of chronic kidney disease with covid -19 was carried out, and an emphasis was placed on rare forms of kidney damage that can develop with covid -19. Attention is paid to aspects of etiopathogenesis and the clinical picture of kidney damage in covid -19. The authors, when writing the article, globally did not touch upon the treatment of renal pathology formed during covid -19, since it is currently mainly reduced, on the one hand, to the treatment of a specific form of kidney disease, on the other hand, to the treatment of the coronavirus infection itself. Understanding the processes of alteration of kidney tissue cells in this disease may help in the future to determine approaches to the prevention of kidney damage and the restoration of their function in patients who are ill or have had covid -19.